Anxious for Nothing : Finding Calm in a Chaotic World - Lucado, Max (Nashville, Tennessee : Thomas Nelson, 2017)
"In the characteristic tone of his previous books like You'll Get Through This and Fearless, Max guides readers through this Scripture passage and explains the key concepts of celebration, asking for help, leaving our concerns, and meditating."--Amazon.com.
Does the uncertainty and chaos of life keep you up at night? Chances are, you or someone you know seriously struggles with anxiety. Lucado invites readers to delve into Philippians 4:6-7: Do not be anxious about anything, but in every situation, by prayer and petition, with thanksgiving, present your requests to God. Lucado explains the scripture, and shows that, though anxiety comes with life, it doesn't have to dominate your life.
Less fret, more faith -- Rejoice in the Lord's sovereignty -- Rejoice in the Lord's mercy -- Rejoice in the Lord always -- Contagious calm -- Prayer, not despair -- Great gratitude -- God's peace, your peace -- Think about what you think about -- Cling to Christ -- C.A.L.M.
Includes bibliographical references.
Keywords: Anxiety -- Religious aspects; Worry -- Religious aspects